An investigation into the management of depression in patients with late-stage cancer by South African oncologists - Fourie, Johanna (Department of Public Health and Family Medicine, 2019)
There are currently more people living with cancer than ever before. The management of the heavy symptom burden carried by these patients remain a critical subject. Of these symptoms, depression is one of the most frequently reported and debilitating symptoms in advanced cancer. The negative impact of untreated depression on both the patient and the healthcare system is well documented. The aim of this study was to explore how South African radiation oncologists manage depression in their late-stage cancer patients. The study focussed specifically on the use of screening tools, their choice of drugs and the mental health resources available to them. A convenience sample of 34 South African radiation oncologists that included participants from both the private and government sector completed an online questionnaire. The results from this study showed that these oncologists do encounter depression in their late stage cancer patients confirming the importance of the subject. While the lack of a universally agreed screening tool remains a problem, at least fifty percent of the respondents were already using some form of screening tool and thirty-five percent of the rest indicated their interest in implementing depression screening in their practice. When faced with a depressed patient, Seventy-four percent of these oncologists felt confident in starting antidepressants and all of them had some sort of mental health resources available to them. Unfortunately, the small study sample and self-reporting lead to concerns regarding the generalizability and validity of the study. However, the study remains valuable in its role of raising awareness for depression in our cancer population, identifying the shortcomings in our current management as well as identifying education needs in our health-care personnel.